Nilai-Nilai Moral Dalam Syair Cinta Rasul Al-Busiry - Ika Selviana; Hendra Irawan (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2020)
The idea of ​​morality in literature is often regarded as something that can damage the value of literary beauty. Many of the writers prioritize the value of beauty and express creativity in literary works freely without involving morality as a learning goal for the reader. ‘Cinta Rasul’ Al-Busiry's poem is a proof that literary works are not only intended for entertainment or beauty functions, but also morality and religion. This is the five functions possessed by literature, ‘recreatif’ (entertainment), ‘didactif’ (education), aesthetics (beauty), morality, and religious. This Old Arabic poem, is not merely the theme of praise the Prophet Muhammad. But it also contains diverse moral values ​​if examined in greater depth and detail. Besides the beauty of language, many moral messages and religious knowledge can be picked up in each of these verses. A small part of moral values is wisdom, courage, self-preservation, and honesty.